2014
DOI: 10.3904/kjim.2014.29.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of nuclear factor κB and chemokine receptor CXCR4 expression in patients with diffuse large B-cell lymphoma who received rituximab-based therapy

Abstract: Background/AimsThis study investigated the expression of nuclear factor κB (NF-κB) and the chemokine receptor (CXCR4) in patients with diffuse large B-cell lymphoma (DLBCL) who received rituximab-based therapy.MethodsSeventy patients with DLBCL and treated with rituximab-CHOP (R-CHOP) were included, and immunohistochemistry was performed to determine the expression of NF-κB (IκB kinase α, p50, and p100/p52) and CXCR4. To classify DLBCL cases as germinal center B-cell-like (GCB) and non-GCB, additional immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Moreover, most previous studies have evaluated only a subset of the NF-κB subunits. [8][9][10][11][12][13][14][15] There are only two studies using all five subunits in DLBCL-a cohort of 88 patients with DLBCL by Odqvist et al 16 and a cohort of 45 patients with testicular DLBCL by Menter et al 17 In the current study, we evaluated expression of all five subunits of the NF-κB protein by immunohistochemistry and its clinical implications in a large cohort of patients with de novo DLBCL.…”
mentioning
confidence: 98%
“…Moreover, most previous studies have evaluated only a subset of the NF-κB subunits. [8][9][10][11][12][13][14][15] There are only two studies using all five subunits in DLBCL-a cohort of 88 patients with DLBCL by Odqvist et al 16 and a cohort of 45 patients with testicular DLBCL by Menter et al 17 In the current study, we evaluated expression of all five subunits of the NF-κB protein by immunohistochemistry and its clinical implications in a large cohort of patients with de novo DLBCL.…”
mentioning
confidence: 98%
“…In this study, although both CXCR4‐ mutated and non‐mutated cases showed CXCR4 expression, the 12 mutated cases showed higher expression of CXCR4, which was independent of the CXCR4 mutation type (Poulain et al , ). In addition, CXCR4 expression in other lymphomas has been studied by immunohistochemistry, but the localization of the protein was not described (Shin et al , ; Cai et al , ).…”
Section: Cxcr4 Staining Pattern Correlates To Cxcr4 Mutation Status Amentioning
confidence: 99%
“…Increased CXCR4 expression was associated with worse survival in both ABC and GCB subtypes for 468 patients treated with the standard therapy R-CHOP [163] and a separate study of 94 patients found that those positive for CXCR4 has reduced survival and increased recurrence of disease [164]. However, a smaller cohort of 70 Korean patients did not identify an association between CXCR4 expression and survival [165]. At the cellular level, strong nuclear CXCR4 staining was correlated with systemic DLBCL whereas strong cytoplasmic CXCR5 staining was correlated with CNS involvement [166].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
“…Furthermore, hypoxia was associated with upregulation of CXCR4 protein [167] and such an increase in CXCR4 expression is believed to increase cell dissemination [164]. IHC revealed that 80% of patients had CXCR4 coexpressed with NF-κB [165], which is often mutated in DLBCL, while CXCR4 itself contains an AIDCA somatic hypermutation hotspot that is suspect to mutation [168]. Various therapeutics targeting CXCR4 in DLBCL have been studied including the CXCR4 antagonist plerixafor which enhanced rituximab treatment [169], BTK140 which inhibited growth in cell lines [163], PIM inhibitors which impaired proliferation and CXCR4-mediated migration [170], and in vivo blocking of CXCR4 which was critical for regulatory T cell attraction to lymphoma [171].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation